Okun's law under the demographic dynamics of the Turkish labor market - Evren Erdoğan Coşar; Ayşe Arzu Yavuz (Central Bank Review (CBR), 2021)
This study examines the asymmetric relationships between demographic characteristics of labor market variables and Gross Domestic Product (GDP) in the Turkish economy. Both expansions and recessions are considered in a Markov Switching (MS) model, using quarterly data between 1989 and 2019. Okun's coefficients are estimated for the different age groups, genders and education levels. The results reveal that men are more likely to lose their jobs during recessions in Turkey whereas unemployment rates for 25-39 year-olds and those with at least university degrees are the least affected groups. There is also asymmetry within and between states across the demographic groups due to GDP phases. The study also investigates the gender dynamics of labor force participation rates (LFPR) as a fundamental determinant of unemployment rate. According to the MS models, LFPR responds significantly and positively to GDP expansions for men whereas it is significant and negative for women. That is, as economic activity begins to recover after a recession, Turkish women leave the labor force as secondary income earners.
Keywords: E32; J21; J64; 330; Demographic composition; Okun's law; Turkey